Cardiovascular diseases managment («Internal medicine» Module 2). Guide. Part 2 - Berezin, A. E.; Vizir, V. A.; Demidenko, O. V.; Березін, Олександр Євгенійович; Візір, Вадим Анатолійович; Деміденко, Олександр Вікторович (Запорізький державний медичний університет, 2021)
The guide was developed for students of 5th courses of medical faculties and combines valuable educational information for topics in the fields of cardiovascular diseases incorporated into the discipline of "Internal Medicine". The guide consists of selected chapters, such as pulmonary thromboembolism, valvular heart disease, cardiomyopathies, myocarditis, infective endocarditis, as wel as diseases of pericardium, which covers most common problems of these diseases based on current evidence and time-tested methods in clinical practice.
Серцево-судинні захворювання: модуль 2. Ч. 2